2019
DOI: 10.3390/su11195206
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Significant Risks and Analyzing Risk Relationship for Construction PPP Projects in China Using Integrated FISM-MICMAC Approach

Abstract: To meet the growing demand for public facilities and services, many developing countries, including China, have adopted the concept of public–private partnership (PPP). However, there are many risks in PPP projects. Furthermore, these risks affect each other, which may lead to project failure. However, the existing research on the PPP risk relationship has not gone into sufficient detail. Therefore, in order to fill this literature gap, this study proposes a procedural method to analyze the correlation between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 84 publications
(144 reference statements)
0
56
0
Order By: Relevance
“…However, BN model shows good performance in data processing, and has no requirements for sample size and information integrity [ 42 , 43 ], and has a mature foundation in dealing with uncertainty problems. At the same time, FISM can transform fuzzy concepts and views into a visual graph model with good structural relationship [ 44 , 45 ], which can intuitively express the relationship between the influencing factors. Therefore, FISM and BN are combined to analyze the hidden cost of prefabricated buildings.…”
Section: Methodsmentioning
confidence: 99%
“…However, BN model shows good performance in data processing, and has no requirements for sample size and information integrity [ 42 , 43 ], and has a mature foundation in dealing with uncertainty problems. At the same time, FISM can transform fuzzy concepts and views into a visual graph model with good structural relationship [ 44 , 45 ], which can intuitively express the relationship between the influencing factors. Therefore, FISM and BN are combined to analyze the hidden cost of prefabricated buildings.…”
Section: Methodsmentioning
confidence: 99%
“…The use of the integrated interpretive structural modelling (ISM) and cross-impact matrix multiplication applied to classification (MICMAC) techniques by researchers in the area of construction has been gaining ground in recent years. Quite a number of researchers in the field of construction [26,[46][47][48][49][50][51][52][53][54] have used the interpretive structural modelling (ISM) and cross-impact matrix multiplication applied to classification (MICMAC) techniques to examine the hierarchical structure between the impediments to a given system or process. Also, the techniques have been used to transform the impediments into clearly visible, easy to understand and quickly interpretable models, based on direct and indirect relationships among the impediments of a system.…”
Section: Methodsmentioning
confidence: 99%
“…In this vein, Hachicha and Elmsalmi [37] proposed an integrated approach based-structural modeling for risk prioritization in the supply network management. In this context, Jiang et al [38] identified a significant risk and analyzing risk relationship for construction projects in China. As for Troche-Escobar et al [39], they studied the SCRM in the Brazilian Wind Power Projects.…”
Section: The Supply Chain Risk Managementmentioning
confidence: 99%